HUBUNGAN PENERAPAN PROGRAM FULL DAY SCHOOL DENGAN PENGEMBANGAN NILAI-NILAI KARAKTER SISWA : Studi Deskriptif Korelasional terhadap Siswa SMA Negeri 1 Cicalengka - Rohaeni, Andi Siti (2017)
This present study aims at determining the correlation between the implementation of full-day school program and the development of student character values at SMA Negeri 1 Cicalengka, Bandung Regency, through the formulated research problems, namely "Is there a correlation between the implementation of full-day school program and the development of student character values at SMA Negeri 1 Cicalengka?". In particular, this present study is intended to answer the issues on: 1) How is the implementation of full day school program implemented at SMA Negeri 1 Cicalengka? 2) How is the development of student character values implemented at SMA Negeri 1 Cicalengka? 3) Is there a significant correlation between the implementation of full-day school program and the development of student character values in the aspects of religion, discipline, reading, and hard work at SMA Negeri 1 Cicalengka?. This carried out study employed a descriptive correlational method, using a quantitative approach. The instruments of data collection were in the forms of questionnaires, observation, and documentation studies. In addition, the samplings were taken using a stratified sampling technique involving 87 students as the samples in this study. In regard to the data analysis, the data were analyzed using the techniques of calculating the research scores, normality test, hypothesis test with correlation analysis, and significance test. Based on the results of this study, it can be concluded that: 1) the implementation of full day school program at SMA Negeri 1 Cicalengka were included in the category of strong score interpretation viewed from the aspects of planning, implementation and evaluation; 2) the development of the student character values in the aspects of religion, discipline, reading, and hard work atat SMA Negeri 1 Cicalengka were in the category of strong score interpretation; 3) there was a significant correlation between the implementation of full-day school program and the development of character values in the aspects of religion, discipline, reading, and hard work.---- Penelitian ini bertujuan untuk mengetahui hubungan penerapan program full day school dengan pengembangan nilai-nilai karakter siswa di SMA Negeri 1 Cicalengka Kabupaten Bandung melalui permasalahan yang telah dirumuskan, yaitu "Apakah terdapat hubungan antara penerapan program full day school dengan pengembangan nilai-nilai karakter siswa di SMA Negeri 1 Cicalengka?". Secara lebih rinci penelitian ini menjawab permasalahan mengenai: 1) Bagaimana gambaran tentang penerapan program full day school di SMA Negeri 1 Cicalengka? 2) Bagaimana gambaran tentang pengembangan nilai-nilai karakter siswa di SMA Negeri 1 Cicalengka? 3) Apakah terdapat hubungan yang signifikan antara penerapan program full day school dengan pengembangan nilai karakter siswa aspek religius, disiplin, gemar membaca, dan kerja keras di SMA Negeri 1 Cicalengka?. Penelitian ini menggunakan metode deskriptif korelasional dengan pendekatan kuantitatif. Instrumen pengumpulan data berupa angket, observasi, dan studi dokumentasi. Teknik pengambilan sampel yang digunakan adalah teknik stratified sampling dengan jumlah sampel sebanyak 87 orang siswa. Teknik analisis data yang digunakan adalah menghitung skor penelitian, uji normalitas, uji hipotesis dengan analisis korelasi dan uji signifikansi. Berdasarkan hasil penelitian di lapangan, dapat diambil kesimpulan: 1) penerapan program full day school di SMA Negeri 1 Cicalengka termasuk dalam kategori interpretasi skor kuat dilihat dari aspek perencanaan, pelaksanaan, dan evaluasinya; 2) pengembangan nilai-nilai karakter siswa aspek religius, disiplin, gemar membaca, dan kerja kerad di SMA Negeri 1 Cicalengka berada pada kategori interpretasi skor yang kuat; 3) terdapat hubungan yang signifikan antara penerapan program full day school dengan pengembangan nilai karakter aspek religius, disiplin, gemar membaca, dan kerja keras.